1993
DOI: 10.1111/j.1399-3054.1993.tb00149.x
|View full text |Cite
|
Sign up to set email alerts
|

The rate of protein synthesis in needles of Norway spruce (Picea abies): Light stimulation, regulation through photophosphorylation, stress enhancement

Abstract: The incorporation of 14C‐leucine into the total‐protein fraction of needles of Norway spruce (Picea abies [L.] Karst.) during short time incubation was used as a measure of protein synthesis in the light and in the dark. Light saturation curves, obtained for needles of different ages (new flush and 1 and 2 years old) or at different seasons (summer‐winter) followed the Michaelis‐Menten algorithm, exhibiting marked differences with regard to light saturation (Vmax) and the half‐saturation constant (K5. 2). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Additionally, cell wall glycoproteins are enhanced under ozone fumigation in beech, spruce, and pine saplings (Schneiderbauer et al, 1995). Stimulation of protein synthesis as a consequence of stress was also observed in adult spruce trees (Schmitz et al, 1993). These data suggest that an additional synthesis of non-structural proteins, to which defence proteins may have contributed, as a consequence of elevated ozone, was strengthened in spruce but not in old-growth beech trees in the present study.…”
Section: Tablesupporting
confidence: 57%
See 1 more Smart Citation
“…Additionally, cell wall glycoproteins are enhanced under ozone fumigation in beech, spruce, and pine saplings (Schneiderbauer et al, 1995). Stimulation of protein synthesis as a consequence of stress was also observed in adult spruce trees (Schmitz et al, 1993). These data suggest that an additional synthesis of non-structural proteins, to which defence proteins may have contributed, as a consequence of elevated ozone, was strengthened in spruce but not in old-growth beech trees in the present study.…”
Section: Tablesupporting
confidence: 57%
“…Contents of NSP were mostly reduced, whilst total soluble amino compounds increased in shade compared to sun leaves of beech trees. Light stimulates protein synthesis and photophosphorylation is assumed to play an important role for the rate of protein synthesis in Picea abies trees (Schmitz et al, 1993). Eichelmann et al (2005) also showed a decrease in soluble proteins in shade compared to sun leaves of Betula pendula and Tilia cordata and a relative content of Rubisco in soluble protein of about 35 %, with lower contents in shade compared to sun leaves.…”
Section: Light Exposure Effectsmentioning
confidence: 95%
“…The catalase activity was high during the night and low during the day. !t seems that the changes in catalase activity are due to changes in photoinaetivation and in the synthesis of catalase, Prolein synthesis in spruce needles is stimulated by lighl (Schmitz et al, 1993), In other plants catalase synthesis was higher during the day than during the night (Redinbaugh et al, 1990, Henwig et al 1992, When spruce needles are exposed to direct sunlighl in the morning the catalase activity probably decreases because in direct sunlight photoinaetivation of catalase is higher than resynthesis. When the needles are shaded between noon and sunset the catalase activity slowly increases because catalase synthesis seems to be slightly higher than its photoinaetivation.…”
Section: Discussionmentioning
confidence: 99%
“…In early spring, multiplied mitotic activity in embryonic shoot caused the significant enlargement of young shoot (Cesar andBornman 1996, Cesar et al 1997) not followed with equally fast protein synthesis what resulted in decrease of the protein content. New flush was suddenly exposed on light conditions and protein synthesis increased (Schmitz et al 1993). Senser et al (1975) demonstrated that the development of thylakoid system in needle plastids is taking place few weeks after the bud break being complete a month later.…”
Section: Resultsmentioning
confidence: 99%